Night School : A Jack Reacher Novel - Child, Lee (Child, Lee. Jack Reacher novel, 2016)
"It's 1996, and Reacher is still in the army. In the morning, they gave Reacher a medal, and in the afternoon they send him back to school. That night he's off the grid. Out if sight, out of mind."--Book jacket.